(untitled) (Research, Society and Development, 2023)
This study is a narrative literature review and aims to guide pelvic floor dysfunctions also arising from pregnancy and inform the importance of strengthening the PFM during pregnancy for the treatment and prevention of pelvic dysfunctions. In accordance with COFFITO Resolution No. 372, of november 6, 2009 - recognizes Women’s Health as a specialty of the professional Physiotherapist and provides other measures. Through physiotherapy, PA dysfunctions can be avoided with low-cost and minimally invasive treatments, as many of these women stop seeking help/treatment due to fear of interventions causing pain and discomfort or even out of shame.